Strategi Komunikasi Pemasaran Pariwisata Kabupaten Pacitan Di Masa New Normal - Utomo, Bambang Setyo; Pradana, Yoka; Maulana, Risal (JURNAL DESTINASI PARIWISATA; Vol 12 No 2 (2024): VOL 12, NO 2 (2024): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2024.v12.i02.p05, 2024)
The background of this research is the increase in the number of tourist visits to tourism in Pacitan Regency during the new normal period, the increase in visits cannot be separated from the tourism marketing communication process. The purpose of this study was to analyze the Marketing Communication Strategy of the Pacitan Regency Government in promoting Pacitan Regency Tourism during the New normal period. This study uses a qualitative method with a case study approach. Data collection was carried out by interview, observation and documentation techniques. The results of this study indicate that the tourism marketing communication strategy of the Pacitan district government during the new normal period includes 3 aspects, namely using a push strategy by utilizing direct marketing marketing communication tools using media catalogs, booklets, leaflets, direct marketing using Instagram, and planning for making electronic ticketing, personal selling by attending meetings and conferences, conducting tour guide training and coaching traders, organizing creative economy trade fairs in Pacitan Regency, and advertising using billboards. Second, using a pull strategy by utilizing sales promotion marketing communication tools by providing discounts for visitors and sponsoring sports and music events. The third uses a profile strategy by publicizing tourism activities in Pacitan Regency, creating identity media, collaborating with media relations, and holding events. The findings regarding the push strategy and profile strategy are in line with the theory put forward by Scott McCabe, but the findings regarding the pull strategy are not in line with the theory put forward by Scott McCabe. Keywords: Strategy, Marketing Communication, Tourism, Pacitan, New normal